Arabic Advertising on Food Products and Beverages: A Stylistic Analysis dan Semantic Field - Novianti , Lisa; Rifai, Alimudin; R. Saleh, Sriwahyuningsi; Pallawagau, Baso (ELOQUENCE : Journal of Foreign Language, 2022)
Background: Many  foods  and  beverage  products  are  currently  using  Arabic  as advertisements  to  promote  product contents and  explain  how  to  present them in a contemporary language style to make it easier for consumers from across countries. Purpose: This study aims to (1) describe  the process  of forming  Arabic vocabulary advertised on food and beverage products and (2) find out the meaning and style of Arabic used in food and beverage products. Method: This study applies a stylistic and semantic field approach to library research. Primary data was collected and identified through seven product advertisements serving food  and  beverages.  Data  were  analyzed  descriptively  through  the  identification  of vocabulary, analysis of the use of advertising language style, and variants of meaning. Results and Discussion: The results of this study indicate that there is a similarity in the use of imperative sentences in the manner of presenting products, the advertising language used to explain how to present food and beverage products always uses the style of uslub al-Amr (command word) to do something. In addition, the word forms used have ten different meanings according to the context of the sentence. Conclusions and Implications: The results  of  this study have implications for  acquiring new Arabic vocabulary with contemporary advertising language styles, which can be done by studying product presentation instructions.